SUBALTERN RELIGIOUS EXPERIENCE: . - Wilfred, Felix (Journal of Dharma, 1998)
That the prognostic about the demise of religion in the context of secularization has been proved wrong, is to state the obvious. The low tide of religion and its apparent receding have been deceptive. In the 80's, religion has come to occupy the spaces which were short-sightedly perceived to have been cleared of it. Are we to interpret this as a reassertion of fundamentalism? The experience in the last two decades are forcing us to rethink our traditional paradigms of religion vis a vis the society, and view the inter-relationship in a much more complex way